Ensilagem de aveia preta : estabilidade aeróbia, perdas de nutrientes e potencial poluidor do efluente - Silva, Samuel Laudelino (2014)
In the present study, three experiments were carried out. We evaluated the chemical composition of forage and silage and aerobic stability of silage. The effluents generated in the ensiling process and after opening the experimental silo of oat silage (Avena strigosa Schreb.) were subjected to mineral analysis and pollution potential. The works were carried out at the Iguatemi Experimental Farm, State University of Maringá situated in the district of Iguatemi, in Maringá / PR. In the first experiment the objective was to determine the nutritional value and losses of dry matter by gases and effluents in oat silage. It was ensiled in experimental silo with a volume of 0,015 m3. After 60 days the silo were opened and then began the monitoring of aerobic stability for 96 hours. Ended up the evaluation, the oat silage was classified as high aerobic stability. The silage was produced in three sizes of particles (MPS 5.0, 8.0 and 12.0 mm) and three densities (550, 600 and 650 kg/m3) totaling nine treatments with four replications . Fermentation characteristics of silages were within the expected for the cultivation of oats standards. The average dry matter losses were highest at MPS 5 mm and 600 kg/m3 on 5th day, however at the 60 th day the highest loss was recorded in the treatment MPS 8 mm and 650 kg/m3. There were no differences (P < 0.05) for dry matter (DM), organic matter (OM), neutral detergent fiber (NDF), mineral matter (MM), lignin (Lig), hemicellulose (Hem), cellulose (Cel), total carbohydrates (CHO) and buffer capacity (BC), considering the treatment applied. However, differences in the values of crude protein (CP), ether extract (EE), in vitro digestibility of dry matter (IVDDM), and acid detergent fiber (ADF) were observed. The second experiment aimed to evaluate the aerobic stability of oat silage, harvested at three particle sizes and ensiled at three densities. The third experiment aimed to characterize, via physicochemical and biochemical analyzes, the nutrient losses, and establish the potential polluter caused byeffluent from oat silage. Analyses were performed in the silage effluent extracted from fresh forage (EFF), at the end of monitoring aerobic stability (SAS) and thirteen days after the end of stability in nine silo which received 50 ml of water per kilogram of silage. The extracted effluent were subjected to analysis of mineral Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca), Magnesium (Mg), Sodium (Na), Copper (Cu), Zinc (Zn), Iron (Fe) and Manganese (Mn). We analyzed the parameters for determining the effect of pollution, namely: pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), Ammonia Nitrogen Kjeldahl test (ANKT), Nitrate (NO3-) and total Phosphorus (P). By the data interpretation, we can infer the following order of pollution potential for the three sets of samples APF < SFE < SFA. These effluents of oat silage showed a relationship COD/BOD greater than 2 indicating the existence of non - biodegradable organic matter which negatively impacts the environment.